Jejak Dharma di Era Modern: Vihara Gayatri dan Pencarian Makna Identitas Kaum Muda - Devi Deliyanti; Muhammad Sairi (Inklusiva: Jurnal Studi Agama-Agama, 2025)
Vihara Gayatri is understood not merely as a place of worship, but as a spiritual and social space that plays a significant role in shaping the religious identity of young Buddhists. This study aims to analyze the symbolic meaning and the role of religious traditions in Vihara Gayatri, Depok, in the process of forming the religious identity of Buddhist youth amid the tide of modernization. Using a qualitative method with an anthropological approach, data were obtained through in-depth interviews with temple administrators, a romo (spiritual leader), young devotees, and visitors, supported by field observation and literature review. The findings reveal that the traditions practiced at Vihara Gayatri such as the Seven Wells ritual, the lighting of the Great Candle, and Dhamma learning activities are perceived as means of spiritual purification, moral cultivation, and social cohesion. The water from the seven wells symbolizes inner cleansing, the Great Candle represents wisdom and enlightenment, while Dhamma activities serve as a medium for internalizing Buddhist teachings. These findings align with Erik Erikson’s psychosocial identity theory, which emphasizes the role of social experience in identity formation, and demonstrate how the vihara functions as a symbolic system that reinforces the religious identity of Buddhist youth within a dynamic cultural and spiritual context.